MENGENAL ṢIGAT-ṢIGAT DALAM MEREPRESENTASIKAN HADIS: - Mulizar (Al-Bukhari : Jurnal Ilmu Hadis, 2019)
In terms of sanad and matan, or based on the strengths and weaknesses, the Hadith is divided into two groups, namely: the hadith maqbūl and the hadith mardūd. One way to find out a hadith whether the hadith is accepted or mardūd can be seen from the Ṣīgāt. Ṣīgāt Hadith is divided into two groups, namely Ṣīgāt Jazm and Ṣīgāt Tamrῑḍ. An assessment of a Hadith is incomplete if we have not discussed ṣīgāt al-Jazm and ṣīgāt at-Tamrῑḍ. This needs to be done to understand how the Hadith is classified. In determining the laws of ṣīgāt al-Jazm and ṣīgāt at-Tamrῑḍ the Ulama of Hadith have explained that if the Hadith is a hadith ḍa’īf, then it is not allowed to exchange it with active sentences ( ṣīgāt al-jazm) such as: said the Messenger of Allah. mention the narration of the hadith ḍa’īf from the tabiin circles by using ṣīgāt al-jazm, but by using ṣīgāt at-tamrῑḍ as the words qῑla, ruwiya, ḥukiya and so forth. This article provides knowledge to the reader, namely how to recognize the traditions through the ṣīgāt expressed in a hadith and give insight to the traditions that are ambiguous and mardūd through ṣīgāt in a hadith, and express how the opinion of the hadith scholars about the ṣīgāt.